Exploring The Socioeconomic Impacts Of Sustainable Entrepreneurship In Indonesia - Benardi Benardi (LPPM STIE Kasih Bangsa, 2024)
This research explores the socioeconomic impacts of sustainable entrepreneurship in Indonesia. Sustainable entrepreneurship is increasingly recognized as pivotal for economic development, job creation, and environmental sustainability, particularly in emerging economies. The review synthesizes findings from existing literature to highlight how sustainable enterprises in Indonesia contribute to innovation, productivity enhancement, and the creation of employment opportunities. Drawing parallels with experiences in Anglophone and Francophone countries, the review examines contextual factors such as institutional quality, regulatory frameworks, and historical legacies that shape entrepreneurial outcomes. Key barriers hindering sustainable entrepreneurship in Indonesia, including access to finance, infrastructure deficiencies, regulatory complexities, and gaps in entrepreneurial education, are identified. The review underscores the importance of improving governance, strengthening legal systems, and fostering an enabling environment to support sustainable business practices.